Pengaruh Kualitas Produk dan Harga terhadap Keputusan Pembelian T-Shirt (Kaos) pada Outlet Temphoyac Kota Jambi - Naofal Dwi Andri (Universitas Batanghari Jambi, 2019)
This research discusses the quality of the product and the price Of the purchase of a t-shirt at the Outlet of Temphoyac in Jambi city. The object of this research is the Outlet Temphoyac in Jambi city in the period 2013-2017. The type of data in this research using primary data and secondary data, can be used by using a questionnaire and literature such as books, newspapers, magazines, and information related to issues that are being discussed.The population in this research is the entire consumer outlet temphoyac Independent of Jambi city in 2017 as many as 8438. the sample in this research is the 99 people. By using qualitative descriptive method. Analysis tools is Multiple Linear Regression Equation with the support by SPSS software 20.0 beside that also in a classical assumption test and hypothetical test to find out the significance of the dependent variable to the independent variables with The F-test, t-test and a test of determination. Based on this research shows that the results was the requirements in a classic assumption test approved. The hypothetical test showhs that tcounton product quality variables (X1) is 6,249 and (X 2)with a significance level of 2,664 is 0.000. Because the tcount 6,249 and 2,664> ttable 1.984 and significance level of 0.000 significance probability < a = 0.05. then Ho denied Ha received. This means the variable quality of the product and the price of individual positive and significant effect against the purchasing decision. Conclusion this research Investigation the product quality on a t-shirt Temphoyac of 99 respondents score was 322 and prices on t-shirt Temphoyac of 99 respondents 361,25 his score and includes the category of